PERAN PEMERINTAH DALAM PEMBERDAYAAN KELOMPOK TANI DI KABUPATEN JENEPONTO - Selviana, Selviana; Burhanuddin, Burhanuddin; Rahim, Samsir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This study aims to determine the role of the government as a regulator, dynamicator and facilitator in empowering farmer groups in Turatea Timur Village, Tamalatea District, Jeneponto Regency. Researchers use phenomenological types to find out what problems occur and develop information and obtain data obtained by researchers during in-depth interviews. The results showed that related to the Government's Role in Empowering Farmer Groups in Turatea Timur Village, Tamalatea District, Jeneponto Regency, it had not been fully implemented optimally. it's just that the implementation is not entirely good because there are still those who have not carried out the rules in accordance with applicable regulations. The government as (2) dynamo, namely (a) Socialization, (b) Assistance, (c) Training, and (d) Field Visits which also cannot be said to be fully optimal because there are still several obstacles in its implementation. And the Government as (3) a facilitator who provides superior seeds, fertilizers and production facilities has been able to facilitate farming communities quite well.